ISOLASI METABOLIT SEKUNDER DAN UJI TOKSISITAS EKSTRAK METANOL KULIT BATANG TANAMAN Cerbera odollam Gaertn. (APOCYNACEAE) - Wina Noviana Widaningsih; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cerbera odollam  Gaertn. was used in traditional medicine as a laxative and antipyretic treatment of dysuria. This Apocynaceae family member contains terpenoid, steroid,   and several other chemical constituents, including iridoid that allegedly have cytotoxic activity. The  n-hexane and methanol macerating method was applied to isolate the secondary  metabolites  from the stem bark of this plant. The separation was carried out by vacuum liquid chromatography (VLC) and gel chromatography respectively. Characterization of the fractions was established using UV-Vis, FTIR, NMR,  and HR-MS spectroscopy which  produced a colored orange needless  cerbinal compound with melting point 188-189 0C. Toxicity assay was conducted by Brine Shrimp Lethality Test  (BSLT) method. The LC50 of 2nd, 3rd, 4th, 8th, 10  th, and  11th fractions of  each methanol extract  were  151.2; 56.96; 30.95; 3.37; 63.02 and 101.03 ppm, respectively. The 5th, 6th, and 9th fractions were not toxic  whereas other fractions were toxic and potential to be used as an anticancer.